AN ALTERNATIVE METHOD OF PREVENTING COASTAL EROSION IN KERASIAN ISLAND - Yulian Firmana Arifin; Gusti Ihda Majaya; Muhammad Noor Azhari; Ellyn Normelani (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2020)
In 2013, Kerasian Island experienced erosion, which caused the coastline to shift Â± 100 m from the initial condition. In some places, the retaining wall has been damaged so that it does not function properly. An effort is needed so that the beach does not experience abrasion and is safe for the activities of residents or tourists who come there. Before deciding on an alternative, first of all, is to choose from many erosion prevention methods that are suitable for the beach conditions there. The selection was conducted using the Analytical Hierarchy Process (AHP) method. Based on the AHP method, groin combined with mangrove planting is a suitable method to be applied on Kerasian Island. The groin design refers to the Pd T-04-2005-A guidelines issued by the Indonesian Ministry of Public Works. The dimensions of the design results and groin material used are explained in detail in the paper.